The dynamic interface of bioarchaeology and forensic anthropology - Ubelaker, Douglas H. (2016)
The disciplines of bioarchaeology and forensic anthropology pursue somewhat different goals but they share considerable methodology and basic scientific information. Experience and research in each of these endeavors enhances the practice of the other. The symbiotic and dynamic relationship of these academic areas greatly improves the quality of the applications of each. The shared information impacts in positive ways all areas of both fields, but is especially important in several key components. Within bioarchaeology, information from forensic practice is vital to the proper interpretation of traumatic and other alterations, especially in the assessment of the timing (antemortem, perimortem, postmortem) of the event producing the alteration. Within forensic anthropology, data gleaned from the practice of bioarchaeology augment techniques of detection, recovery and assessment of the postmortem interval and taphonomic factors that may be involved. Currently, both fields are experiencing a surge in professional activity and student interest, as well as a rapid increase in published research, casework and technology. While the volume of available information presents challenges, practitioners in each field need to remain cognizant of professional activity and research results in the other.